Особенности педагогического общения - Ivleva T. V. (Pedagogical excellence and pedagogical technologies, 2017)
The article is devoted to a problem of pedagogical communication which is one of the most difficult and many-sided phenomena in the field of education. The author calls a variety of reasons which prevent to perceive and estimate pupils correctly. In article a property, plant and equipment of pedagogical communication which in case of the correct use will help the teacher to avoid many difficulties are studied.
Keywords: стереотип; педагогическое общение; аспект; stereotype; личностный барьер; этические ценности; pedagogical communication; personal barrier; aspect; ethical values